Finding the Balance Between Simplicity and Realism in Participatory Modeling for Environmental Planning. (November 2022) - Zellner, M.L.; Milz, D.; Lyons, L.; Hoch, C.J.; Radinsky, J.
Abstract: Complex systems simulations can support collaborative water planning by allowing stakeholders to jointly see hidden effects of land- and water-use decisions on groundwater flow. We adopted a participatory modeling progression where stakeholders learned to modify and use increasingly sophisticated models to assess policy impacts on groundwater levels. Stakeholders' shared understanding of the problem and the novelty, concreteness, and richness of proposed solutions evolved alongside the models' degree of realism, but up to a certain point. More realistic models became a distraction and stymied efforts to plan for water shortages. The reflective learning required to plan for complex environmental problems is best supported by models that strike a balance between representational fidelity and end-user intelligibility. Complicated models and high-resolution data may overwhelm model users, preventing them from acting on the useful planning insights they derived from the exploratory modeling, particularly within social contexts that exhibit strong power dynamics and favor prediction. Highlights: We study how a developmental participatory modeling approach using increasingly realistic models can support water planning. Stakeholders' problem definition and solution space evolved as they co-developed models with increasing realism. Participants were distracted by excessive details, preventing them from contributing to plan-making and policy formulation. We derive insights to support adoption of environmental modeling in collaborative decision-making processes.